(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Projects are the basic physical and organizational structures necessary for the operation of society or business, like as means of transportation such as roads, airports, railways, and means of communication such as the telephone network, mobile phone, Internet, and post, in addition to the sewage system and water installations. And how to measure the losses resulting from stopping projects and their reluctance and the productive life of a project in addition to clarifying the relationship between project delay and financial and social damages and what are the proposed solutions in order to complete projects as quickly as possible, and the importance of research stems from dealing with waste of money due to stalled or stalled projects and delaying treatments resulting from project privatization And his work, and in the intention of reaching the expected research goals, will be based on a number of Arabic and foreign references, research, and periodicals related to the subject of the research in question, as well as taking advantage of the Internet and applying the calculation of extinction on stalled projects, depending on the percentage of extinction and the productive age of the project, which includes the research community roads and palpation The housing estate and public property and its facilities included the research sample (opening Al-Muheet Street at 30 Street in the Saif Saad area, rehabilitation and realization of the basic design of the Wardiya Saif Saad road, a project for designing and implementing the entrance road to Hilla Najaf, opening and leveling streets with different lengths and widths and workshops for a rimcoat layer in the municipality of Al-Kifl, Establishment of the Al-Kifl Municipality Garage Project, a project to construct part of the green belt in Al-Kifl. The study period extended from 4/17/2012 to 12/30/2020. Financing advances for contractors when completing the completed bridges and the amounts of roads and bridges deducted in the Babylon passage are not actually funded for roads and bridges at least in the same governorate. As for the recommendations, they came to control the financial planning process and reserve funds according to their allocations and not to dispose of them in other areas and direct financing of the amounts deducted in the Babylon passage and collection Taken from load cars for roads and bridges.